2016
DOI: 10.1186/s12933-016-0413-6
|View full text |Cite
|
Sign up to set email alerts
|

Metformin improves circulating endothelial cells and endothelial progenitor cells in type 1 diabetes: MERIT study

Abstract: BackgroundType 1 diabetes is associated with increased cardiovascular disease (CVD). Decreased endothelial progenitor cells (EPCs) number plays a pivotal role in reduced endothelial repair and development of CVD. We aimed to determine if cardioprotective effect of metformin is mediated by increasing circulating endothelial progenitor cells (cEPCs), pro-angiogenic cells (PACs) and decreasing circulating endothelial cells (cECs) count whilst maintaining unchanged glycemic control.MethodsThis study was an open la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(91 citation statements)
references
References 54 publications
(63 reference statements)
4
82
0
1
Order By: Relevance
“…Moreover, we previously reported that the indices of vascular health, i.e., cEPC/CD45 dim CD34 + CD133 + cells, PACs, and fibronectin adhesion assay (FAA), were lower in T1DM patients versus HC [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, we previously reported that the indices of vascular health, i.e., cEPC/CD45 dim CD34 + CD133 + cells, PACs, and fibronectin adhesion assay (FAA), were lower in T1DM patients versus HC [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…otherwise known as circulating early endothelial progenitor cells (EPCs). It is well established, including by us, that in both type 1 and type 2 diabetic patients, there are fewer circulating EPCs than in HCs, confirming increased CVD risk [ 4 , 32 ]. EPCs have been proven to promote vascular repair via transmigration to promote new vessel growth and predict future CVD events [ 6 , 33 ].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a single paediatric centre experienced in FMD-and GTN-mediated vascular reactivity [32], with clinical confirmation of the latter in the T1D MERIT study [33].…”
Section: Metformin Improves Vascular Function In Youth With Type 1 DImentioning
confidence: 88%
“…However, impaired colony shaping, differentiation and migration abilities and survival in EPCs were dominated in diabetes across its nature evolution [17]. Indeed, hyperglycemia, insulin resistance and dyslipidemia are main triggers of putative EPC dysregulation by affecting the SDF-1/CXCR-4 and NO pathways and the p53/SIRT1/p66Shc axis that contribute to EPCs mobbing, migration, homing, differentiation and angiopoetic properties [18,19]. As a result altered balance between vascular injury and vascular reparation induces atherosclerosis, microvascular inflammation, pro-thrombotic state and thereby modulates target organ damages including retinopathy, renal disorders, cardiac failure, and peripheral artery disease [11].…”
mentioning
confidence: 99%